Is Depression a Part of The Aging Process?!: A Study From The Old Age Homes in Davangere District, Karnataka - Achappa, Santosh; Varadaraja, Rao BA (National Journal of Community Medicine, 2017)
Background: Depression is a problem of many elderly. Even though attention has been paid to the medical problems of the elderly their social problems demands considerable light in order to improve the quality of their lives. The study was conducted to assess the magnitude of depression among the elderly living in the old age homes and 2. To determine the social factors associated with depression. Methodology: A cross sectional study was carried out in the old age homes of Davangere district for a period of 1 year with the sample of about 105 elderly residing in old age homes. Geriatric Depression Scale (GDS) was used to assess the depression. Socio factors were measured by responses to the pre-tested and semi structured questionnaire. Results: Magnitude of depression among the elderly in old age homes was found to be 50.5%.Among the social factors, there was a statistically significant association between Depression and the literacy status (P = 0.0019) and between Depression and income from any source (P = 0.004). Conclusion: The magnitude of depression is high in the old age homes. There are various social factors that play a role in depression among elderly.